2021
DOI: 10.3389/fmicb.2021.698169
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID or Post-acute Sequelae of COVID-19 (PASC): An Overview of Biological Factors That May Contribute to Persistent Symptoms

Abstract: The novel virus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a pandemic of coronavirus disease 2019 (COVID-19). Across the globe, a subset of patients who sustain an acute SARS-CoV-2 infection are developing a wide range of persistent symptoms that do not resolve over the course of many months. These patients are being given the diagnosis Long COVID or Post-acute sequelae of COVID-19 (PASC). It is likely that individual patients with a PASC diagnosis have different underlying biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
579
3
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 660 publications
(718 citation statements)
references
References 286 publications
17
579
3
7
Order By: Relevance
“…Commonly understood factors include organ damage, persistently dysregulated inflammatory and immune responses, and unrecognised microvascular thrombosis and endotheliitis [ 9 ]. Many other factors have been hypothesised; persistent tissue reservoirs of SARS-CoV-2, re-activation of other viruses, brainstem and/or vagus nerve dysfunctions and activation of autoimmunity due to molecular mimicry between pathogen and host proteins [ 10 ]. In addition, secondary infections (bacterial or fungal), effects of prolonged hospitalisation, sequelae of critical illness, post intensive care syndrome, drug side effects (e.g., corticosteroids), socioeconomic and psychological impact of the illness, may contribute [ 2 , 11 ].…”
mentioning
confidence: 99%
“…Commonly understood factors include organ damage, persistently dysregulated inflammatory and immune responses, and unrecognised microvascular thrombosis and endotheliitis [ 9 ]. Many other factors have been hypothesised; persistent tissue reservoirs of SARS-CoV-2, re-activation of other viruses, brainstem and/or vagus nerve dysfunctions and activation of autoimmunity due to molecular mimicry between pathogen and host proteins [ 10 ]. In addition, secondary infections (bacterial or fungal), effects of prolonged hospitalisation, sequelae of critical illness, post intensive care syndrome, drug side effects (e.g., corticosteroids), socioeconomic and psychological impact of the illness, may contribute [ 2 , 11 ].…”
mentioning
confidence: 99%
“…For example the time needed for the full panel of symptoms to arise (1-2 weeks), coincides with the time needed for the production of autoantibodies (220,221). Persistence of these autoantibodies and/or the accompanying inflammation after the resolution of the acute phase of COVID-19 has also been proposed as a possible mechanism leading to the so-called "long-COVID" (222)(223)(224). On the other hand, it is of interest, that, some of the main drugs used in patients hospitalized with COVID-19 (like corticosteroids, IL6 inhibitors, Jak inhibitors etc.)…”
Section: Discussionmentioning
confidence: 99%
“…While some of the post-acute sequelae may be transient, others are irreversible. In general, symptoms are diverse but often include chronic fatigue, decline in quality of life, neurological symptoms and auto-inflammatory/auto-immune diseases [22,23].…”
Section: What Are Post-acute Sequelae Of Viral Infections?mentioning
confidence: 99%
“…A recent study reported that about 30% of COVID-19 outpatients or hospitalized patients report persistent symptoms [89]. Among these are fatigue, abnormal thermoregulation, skin diseases, intestinal symptoms up to diabetes leading to significant symptom burden and failure to fully recover and return to previous work levels [22,23,[90][91][92][93][94]. Notably, the previously epidemic coronaviruses SARS-CoV-1 and MERS-CoV have induced a similar set of symptoms in their post-acute phase [97][98][99].…”
Section: Post-acute Sequelae Of Covid19 (Pasc)mentioning
confidence: 99%